2018
DOI: 10.1002/maco.201709947
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of stone‐hard‐soil formation from AC corrosion of cathodically protected pipeline

Abstract: A stone‐hard‐soil structure was observed on a metallic pipeline under cathodic protection and subject to alternating current corrosion at a coating defect. Using X‐ray diffraction, energy dispersive X‐ray spectroscopy, ion‐chromatography and inductively coupled plasma optical emission spectroscopy, the stone‐hard‐soil was characterized as being enriched in NaCl. Local alkalization following the cathode reactions caused precipitation of calcite, believed to be partly responsible for the stability of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…[55] The pH of the WE during CP was estimated from corresponding data of pH at a current density of 0.5 A m −2 from the literature. [56][57][58][59][60][61][62][63][64][65][66] The black lines correspond to the equilibrium reactions of the iron species considering a soluble concentration of Fe 2+ in water of 10 −6 M. The dashed line corresponds to the reversible potential of the hydrogen evolution reaction (HER). [Color figure can be viewed at wileyonlinelibrary.com] alkaline conditions at the metal surface upon cathodic polarization has been widely provided in the literature, [55][56][57][58][59][61][62][63]67,68,71,72,75,76] limited experimental evidence is available that simultaneously and directly relates this raise in pH to passive film formation.…”
Section: Cathodic Potentiostatic Polarizationmentioning
confidence: 99%
“…[55] The pH of the WE during CP was estimated from corresponding data of pH at a current density of 0.5 A m −2 from the literature. [56][57][58][59][60][61][62][63][64][65][66] The black lines correspond to the equilibrium reactions of the iron species considering a soluble concentration of Fe 2+ in water of 10 −6 M. The dashed line corresponds to the reversible potential of the hydrogen evolution reaction (HER). [Color figure can be viewed at wileyonlinelibrary.com] alkaline conditions at the metal surface upon cathodic polarization has been widely provided in the literature, [55][56][57][58][59][61][62][63]67,68,71,72,75,76] limited experimental evidence is available that simultaneously and directly relates this raise in pH to passive film formation.…”
Section: Cathodic Potentiostatic Polarizationmentioning
confidence: 99%
“…This causes a cyclic variation of spread resistance, current densities and corrosion rate. The detailed chemical investigation of stone hard soil formed on cathodically protected pipeline under AC interference is reported in [68]. The crucial role of soil chemical composition, pH and spread resistance was carefully investigated by Junker et al [62,[67][68][69].…”
Section: The Alkalization Mechanism and The Effect Of Spread Resistancementioning
confidence: 99%
“…The detailed chemical investigation of stone hard soil formed on cathodically protected pipeline under AC interference is reported in [68]. The crucial role of soil chemical composition, pH and spread resistance was carefully investigated by Junker et al [62,[67][68][69]. The spread resistance is identified as a key parameter, controlling the current densities, and is highly influenced by the formation of calcareous deposits or corrosion products.…”
Section: The Alkalization Mechanism and The Effect Of Spread Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Anonymous [4] and Dang et al [5] introduced the application of cathodic protection systems for pipeline coating defects. Varela et al [6] and Junker et al [7] pointed out the effective methods of anticorrosive coating defects of buried pipelines or corrosion mitigation measures, and they studied the severity and condition of corrosion undercoating defects. Wu et al [8] showed that the improvement of the cathodic protection performance of the coating can be attributed to severe galvanic corrosion.…”
mentioning
confidence: 99%